Ljubljanska and Slavonska Avenue- Traffic Key of the City of Zagreb - Dadić, Ivan; Malić, Adolf; Kos, Goran (Promet - Traffic&Transportation, 2012)
The paper analyses the urban motorway, the Ljubljanskaand Slavonska Avenue in Zagreb. As the key road, it is importantfor the city of Zagreb both regarding internal and externaltraffic links. The almost ideal location of the Ljubljanska andSlavonska Avenue has not been properly evaluated and used bythe Zagreb urban and traffic designers. The traffic count, measuringthe vehicles speed and the analysis of the existing interchangeshave indicated the disadvantages, drawbacks and irregulalitiesrelated to the design of the motorway. The measuresfor improving the traffic flows and change of signalling deviceshave been proposed and the design of interchanges has beenrecommended. The traffic forecast for the next ten years, accordingto the growth predicted by BDP, imposes urgency in realisingthe phases in improving the throughput capacity andsafety of the traffic along this motorway.